2005
DOI: 10.1111/j.0022-202x.2005.23683.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multiple P2X Receptors in Cultured Normal Human Epidermal Keratinocytes

Abstract: ATP-gated ion channels (P2X) are expressed in human epidermis and cultured keratinocytes. The aim of this study was to characterize native P2X receptors in normal human epidermal keratinocytes (NHEK) using whole-cell patch clamp technique, RT-PCR, and determination of intracellular Ca(2+) concentration ([Ca(2+)](i)). Application of ATP resulted in an inward current with a reversal potential of 0 mV. Response to ATP showed two types of currents: the slowly desensitizing response and the rapidly desensitizing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 36 publications
6
52
0
Order By: Relevance
“…Previous studies in human and rat skin keratinocytes have reported the presence of P2X 2 , P2X 3 , P2X 5 and P2X 7 receptor subunits [23,24]. P2X receptors found in the skin are suggested to have an important physiological role as an initial sensor for external stimuli, and P2X 7 receptors, known to be involved in ATP-induced apoptosis, are likely to participate in the process of the end-stage terminal differentiation of keratinocytes [23]. The presence of P2X receptor expression in epidermal basal cells suggests a potential role for P2X receptors in relation to cell growth and differentiation in the equine hoof.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies in human and rat skin keratinocytes have reported the presence of P2X 2 , P2X 3 , P2X 5 and P2X 7 receptor subunits [23,24]. P2X receptors found in the skin are suggested to have an important physiological role as an initial sensor for external stimuli, and P2X 7 receptors, known to be involved in ATP-induced apoptosis, are likely to participate in the process of the end-stage terminal differentiation of keratinocytes [23]. The presence of P2X receptor expression in epidermal basal cells suggests a potential role for P2X receptors in relation to cell growth and differentiation in the equine hoof.…”
Section: Discussionmentioning
confidence: 91%
“…3 Immunostaining for P2X 1 (a, e), P2X 2 (b, f), P2X 3 (c, g) and P2X 7 to enable it to function in its roles within the suspensory apparatus of the distal phalanx in equids [22]. Previous studies in human and rat skin keratinocytes have reported the presence of P2X 2 , P2X 3 , P2X 5 and P2X 7 receptor subunits [23,24]. P2X receptors found in the skin are suggested to have an important physiological role as an initial sensor for external stimuli, and P2X 7 receptors, known to be involved in ATP-induced apoptosis, are likely to participate in the process of the end-stage terminal differentiation of keratinocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…P2Y1 and P2Y2 receptors expressed in basal layers of the fetal and adult epidermis [111,113] were immune colocalized with the cell proliferation markers Ki67 and PCNA (proliferation cell nuclear antigen) [111]. The P2Y1 receptor agonist 2-methylthio-ADP (P2Y1 agonist) and UTP activating P2Y2 receptors induced proliferation in cell cultures of basal keratinocytes [113].…”
Section: Skin Injurymentioning
confidence: 99%
“…Two important functions are attributed to this nucleotide such as modulation of keratinocyte proliferation and differentiation [110]. Many studies have shown that these effects are mediated by ATP action through P2X and P2Y receptor subtypes, and it is known that the epidermis expresses P2X5, P2X7, P2Y1, and P2Y2 subtypes with diverse functions [111][112][113].…”
Section: Skin Injurymentioning
confidence: 99%
See 1 more Smart Citation